Government Debt, Government Spending and Private Sector Behavior Revisited: Comment - Feldstein, Martin; Elmendorf, Douglas W. (American Economic Review, 1990)
Perhaps no issue has generated as much controversy among economists in the past decade as the proposition that an increase in the government deficit induces an equal offsetting increase in private saving. The truth of this so-called Ricardian equivalence proposition is central to whether budget deficits reduce capital accumulation, to the feasibility of expansionary tax reductions, and to the effects of Social Security on private saving and aggregate capital accumulation. Although the basic idea that the future tax liabilities associated with government deficits and debt induce individuals to increase their saving has been around since the time of David Ricardo and was treated explicitly by Don Patinkin (1965), Martin Bailey (1971) and Levis Kochin (1974), the current debate was launched by Robert Barro (1974). The voluminous theoretical literature of recent years has shown that complete Ricardian equivalence would be expected to prevail only under very special conditions; see Douglas Bernheim (1987) for an especially useful survey and analysis. But the theoretical restrictiveness of the assumptions required for complete Ricardian equivalence does not constitute a practical refutation. Defenders of Ricardian equivalence can argue that the theory is only an approximation and can claim that, although the stringent conditions required for complete Ricardian equivalence do not hold, the economy's behavior in practice is close to the predictions of Ricardian equivalence. There are two key empirical questions. The first is whether a higher level of taxes (with government spending constant) induces individuals to reduce their spending on consumption as traditional theory holds or has no effect on consumer spending as the Ricardian equivalence proposition predicts. The second deals with the effect of government outlays on goods and services. Although the absence of a negative effect on consumer spending of such government outlays is clearly contrary to the Ricardian equivalence proposition, the existence of a moderate negative effect of government outlays on consumer spending is not in itself evidence in favor of the Ricardian equivalence proposition that individuals increase their saving to finance anticipated debt service. As Feldstein (1982) explained, consumers may correctly believe that a rise in current government spending is a good indicator of a higher level of future government spending. Once a program is launched or budgets increased, the process is unlikely to be reversed. An increase in current government spending is therefore a good indication that future taxes will have to be higher to finance a higher level of future government spending. Individuals may rationally reduce their own spending when government outlays increase without a concurrent increase in taxes because they anticipate higher future taxes to finance higher future government spending even if they give little or no weight to the debt service implications of the current deficit. The strongest direct evidence in favor of Ricardian equivalence is Roger Kormendi's 1983 article in the American Economic Review. He presents consumption regression equations that relate an estimate of consumption' to net national product, wealth, *Martin Feldstein is Professor of Economics at Harvard University and President of the National Bureau of Economic Research. Douglas Elmendorf is Assistant Professor of Economics at Harvard University. We are grateful to Greg Mankiw and Lawrence Summers for comments on an earlier draft. The research reported here is part of the NBER study of the Government Budget and the Private Economy. 'iKormendi defines consumption as the sum of current expenditures on services and nondurables plus 10